MATERNAL PATIENT EXPERIENCE AND INTENTION TO REVISIT: A STUDY IN A PRIVATE HOSPITAL IN MALANG CITY - Oktaviana, Ratih; Setijowati, Nanik; Aminingrum, Rahmawati (Universitas Brawijaya, 2025)
Maternal health care is an important component of the national health system since it directly affects maternal and child health. The quality of maternal care is evaluated not only based on clinical outcomes, but also on the patient's experience with the preceding treatment. This experience encompasses emotional factors, interactions with health care providers, hospital facilities, and service accessibility. Patients who have pleasant pregnancy, delivery, and postpartum experiences are more likely to revisit and use the same health services in the future. This study employs a qualitative methodology with a phenomenological approach. Data was collected through in-depth interviews with seven outpatients chosen based on particular criteria at the gynecological clinic at X Hospital in Malang City. The data were evaluated using thematic analysis, which involved categorizing interview results based on themes that arose in line with the research objectives. The findings of this study indicate that pregnant patients desire to revisit to Hospital X for a variety of reasons, including the availability of qualified specialist doctors, comprehensive facilities and infrastructure, good and courteous staff service, and the hospital's Islamic brand image. The majority of the informants expressed great happiness and satisfaction with their interactions at this facility. However, there were also less pleasant encounters, such as long and inconvenient lines and doctors who arrived late. Exploring the experiences of these maternal patients is one of the initiatives to find measures to boost patients' intent to visit this hospital again.